Effects of Rhizobacteria on the Nutritional Status of Blackberry Cultivars Grown in Calcareous Soil Conditions - İpek, Muzaffer; Eşitken, Ahmet; Arıkan, Şeyma; Pırlak, Lütfi (Erwerbsobstbau, 2024)
Limestone soils, which possess restricted solubility of microelements such as iron, manganese, zinc, and copper, cover 30% of the earth’s land surface. Chlorosis is a devastating disease that can drastically reduce agricultural yields. As a result, the farmer must use more expensive fertilizer to resolve the problem, increasing the cost of producing the crop. In the present study, it was found that treatment T8 (T8:637Ca+SY48+SY55) was found to be more effective in terms of nutrient supply to the plants in both blackberry cultivars. The nitrogen, phosphorous, and iron content (2.14–4.03%, 0.40% and 125.54 mg kg−1) were found to be highest in ‘Chester’ as compared to cultivar ‘Jumbo’ (1.93–3.62%, 0.37% and 112.90 mg kg−1), respectively. Copper content varied between 6.42 mg kg−1 and 14.55 mg kg−1 in the ‘Chester’, while it varied from 5.77 mg kg−1 to 13.09 mg kg−1 in the ‘Jumbo’ cultivar. The positive effects of rhizobacteria have been the subject of research, especially in arid, saline, and partially calcareous soils. According to the results of this research, it has been seen that positive results will be obtained from the use of bacteria with different abilities in nutrition together.